2020
DOI: 10.3390/d12080307
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Trends of Burnt Area in Angola: Implications for Natural Vegetation and Protected Area Management

Abstract: Fire is a key driver of natural ecosystems in Africa. However, human activity and climate change have altered fire frequency and severity, with negative consequences for biodiversity conservation. Angola ranks among the countries with the highest fire activity in sub-Saharan Africa. In this study, we investigated the spatial and temporal trends of the annual burnt area in Angola, from 2001 to 2019, and their association with terrestrial ecoregions, land cover, and protected areas. Based on satellite imagery, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 74 publications
(127 reference statements)
2
32
0
Order By: Relevance
“…The conservation status has been accessed over the last few years, but only 60.9% (39 of the 64 native species) were already evaluated according to the IUCN criteria 34 . Among them, six are classified in the threat categories (one critically endangered and five endangered) and one as near threatened, but this number is likely to increase in the near future, because the pressure on natural resources continues to increase in most African countries, driven by economic and population growth as well as climate change 41 , 42 . Currently, the specific threats to African native pulses species are not well known 14 , but some studies focusing on the conservation of native biodiversity of African legumes 41 43 identified deforestation, agriculture and urbanization, harvesting for medicinal uses, fires, and invasive species as the main threats.…”
Section: Discussionmentioning
confidence: 99%
“…The conservation status has been accessed over the last few years, but only 60.9% (39 of the 64 native species) were already evaluated according to the IUCN criteria 34 . Among them, six are classified in the threat categories (one critically endangered and five endangered) and one as near threatened, but this number is likely to increase in the near future, because the pressure on natural resources continues to increase in most African countries, driven by economic and population growth as well as climate change 41 , 42 . Currently, the specific threats to African native pulses species are not well known 14 , but some studies focusing on the conservation of native biodiversity of African legumes 41 43 identified deforestation, agriculture and urbanization, harvesting for medicinal uses, fires, and invasive species as the main threats.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trends of burned area are strongly related to changes in fire regimes. This factor is based on the mapping of the positive trend of the area burned annually in Angola, analyzed between 2001 and 2019 (for more details, see Catarino et al., 2020). On the reference map, the significant areas of increasing trends of burned area (at a 95% confidence level) and a 5‐km buffer were classified as 10.…”
Section: Methodsmentioning
confidence: 99%
“…Although wildfires are an important ecological factor in Miombo woodlands, substantial changes in natural fire regimes could be extremely destructive for native flora (Mendelsohn, 2019). Fire frequency has been increasing in recent years, and many anthropogenic fires have occurred in the late dry season, when the trees break dormancy and are more susceptible to damage (Catarino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hammond and Pokorný [7] address the process of succession in a tropical moist semi-deciduous forest, analyzing the diversity of tree species in gap regeneration. The important issue of fire effect on natural vegetation and its implications is presented for Angola by Catarino et al [8], who analyzed the spatial and temporal trends of burnt areas and found increasing trends associated with savannas and grasslands in miombo woodlands' biome.…”
mentioning
confidence: 99%